Etude de l’insuffisance rénale chronique chez les diabétiques - HAMIDA, ASMA; AZREUG, SOUMIA (My University, 2017)
Diabetes is the leading cause of chronic renal failure (CKD) in early stages, nephroprotective therapies associated with glycemic control and lifestyle changes are recommended, but at the end-stage survival is ensured by A supportive treatment: dialysis or renal transplantation. IRC leading to terminal renal failure requiring dialysis or transplantation is a major public health problem. It is therefore important to identify an IRC at an early stage in order to slow down its progression and reduce its consequences. These consequences must be known because their adequate management reduces the associated morbidity: anemia, hyperkalaemia, water overload, the hypernatremia. Hemodialysis is a treatment (HD) meets a vital need for uremic patients must enroll in a comprehensive and long-term. It aims to correct metabolic disorders, ensure the survival of patients.
Keywords: Keywords; Diabetes; Chronic renal insufficiency; hemodialysis; Diabète; Insuffisance rénale chronique; hémodialyse